A Bibliometric Analysis of Global Research Trends in Psoriasis and Metabolic Syndrome - Tang ZJ; Yang JR; Yu CL; Dong MH; Wang R; Li CX (Dove Medical Press, 2024)
Zi-Jie Tang,1,2 Jing-Run Yang,3 Chong-Li Yu,2 Mei-Han Dong,1,2 Rui Wang,2 Cheng-Xin Li1,2 1Graduate School, Medical School of Chinese People's Liberation Army (PLA), Beijing, 100853, People's Republic of China; 2Department of Dermatology, The First Medical Center of Chinese PLA General Hospital, Beijing, 100853, People's Republic of China; 3Department of General Surgery, The First Medical Center of Chinese PLA General Hospital, Beijing, 100853, People's Republic of ChinaCorrespondence: Cheng-Xin Li; Rui Wang, Department of Dermatology, the First Medical Center of Chinese PLA General Hospital, No. 28 Fuxing Road, Haidian District, Beijing, 100853, People's Republic of China, Tel +86-18501969456, Email chengxinlidr@yeah.net; wr0699@163.comBackground: Psoriasis is a frequent form of chronic inflammation in dermatology that is unmistakably linked to the metabolic syndrome (MetS) and its elements. This study was to explore the current status and new developments in the global research, and the holistic landscape of this field more intuitively through bibliometric analysis of scientific output and activity.Methods: Publications regarding psoriasis and MetS were searched and chosen from the database of the Web of Science Core Collection. Excel 2019, VOSviewer, and CiteSpace software were utilized to conduct bibliometric analysis.Results: There were 1096 publications included. The scientific outputs in this field had increased from 2004 to 2022, and the expansion could continue in the following years. The United States contributed the most publications (241, 21.99%) and had the most citation frequency (13,489 times). The University of California System was the most productive affiliation. Girolomoni G., Armstrong A.W., Gisondi P. and Gelfand J.M. were key and influential researchers. Journal of the European Academy of Dermatology and Venereology published the greatest number of articles (65 articles). By analyzing keyword frequency and clustering, we have identified the following areas of research interest and frontiers: prevalence, risk, association, gene expression, waist circumference, adipose tissue inflammation, vascular inflammation, cardiovascular disease, psoriatic arthritis, and fibrosis.Conclusion: This bibliometric analysis elucidates research domain of psoriasis and MetS, portraying present hotspots and future emerging trends. This field has generated significant interest and displays potential for further growth. The United States has made distinguished contributions, and currently dominates this field.Keywords: psoriasis, metabolic syndrome, gene expression, vascular, inflammation